Synthesis and characterization of magnetic nanoparticles Fe3O4@SiO2 decorated with amino groups - Harmand, Lydie; Bhosale, Dattary; Beneš, Ludvík; Palarčík, Jiří; Kalendová, Andréa; Sedlák, Miloš (University of Pardubice, 2014)
The oxidation of ferrous sulfate in aqueous medium was used to prepare hydrophilic nanoparticles of Fe3O4 with the hydrodynamic size of 114 ± 59 nm. By means of sol-gel method, the nanoparticles were coated with a layer of amorphous SiO2, which provided the Fe3O4@SiO2 nanoparticles with the size of 188 ± 36 nm. The reaction of Fe3O4@SiO2 with 3-aminopropyltriethoxysilane resulted in attaching of amino groups to the surface of the particles. During the reaction lasting 1 hour, the original size of particles (190 ± 40 nm) remained unchanged, and the total nitrogen content was 2.21 %, and the nitrogen content corresponding to reactive amino groups was 1.22 %. A prolongation of the reaction time up to 3 hours resulted in production of aggregates and increase in the total nitrogen content up to 3.75 %. However, the content of reactive nitrogen increased only negligibly (1.30 %). The spherical shape of the Fe3O4@SiO2–NH2 particles produced and their hydrodynamic size are suitable for applications to catalysis as well as for biomedical applications.